2053. Tissue-Based Molecular Diagnostics: A Sensitive and Specific Way for the Identification of Invasive Fungal Infections in the Combat-Related Setting. (26th November 2018) - Ganesan, Anuradha; Shaikh, Faraz; Peterson, Philip; Bradley, William P; Johnson, Brian; Bennett, Denise; Carson, Leigh; Merritt, Teresa; Akers, Kevin S; Wells, Justin; Bialek, Ralf; Tribble, David R; et al.
Abstract: Background: Combat-associated invasive fungal infections (IFI) of the deep skin and soft tissue are an infectious disease. Reliance on conventional techniques to diagnose IFIs has limitations as culture is insensitive and time-delayed and histopathology cannot provide a species-level or even a genus-level identification (ID). Molecular-based methods are rapid, provide species-level ID, and have been studied to a limited extent in the trauma setting although they may prove overly sensitive as soil (thereby fungal) contamination is common. In this study, we examined the performance characteristics of a panfungal PCR for the diagnosis of IFI among subjects injured in Afghanistan operations. Methods: Formalin-fixed paraffin-embedded (FFPE) tissue samples obtained during debridement from IFI cases with angioinvasion (AI) and controls (combat-injured with negative histopathology) were evaluated with a panfungal PCR targeting the internal transcribed spacer (ITS 1 and ITS 2) of the fungal genome. Results: We assessed 41 injury sites where culture, histopathology, and FFPE specimens were available contemporaneously. Fungus was cultured from 32 sites (78%) with the order Mucorales represented in 18 sites (44%, five sites with Saksenaea spp.), and Aspergillus spp. in six (15%) sites. Using PCR, a fungus was identified from 33 sites (81%) with order Mucorales identified from 28 sites (68%, 20 with Saksenaea spp.) and Aspergillus spp. from five (12%) sites. When compared with the gold standard (histopathology), the sensitivity, negative, and positive predictive value were 83, 94, and 98%, respectively. Specificity was calculated to be 99.2% based upon the identification of one false-positive among 118 controls. Conclusion: Concerns about PCR being overly sensitive for the diagnosis of trauma-related IFI are not upheld. The PCR-based method was sensitive, specific, and had a high negative predictive value for the diagnosis of AI IFI. Re-demonstrated is the inability of culture to identify fungi of the order Mucorales and the need for antifungal coverage targeting fungi of the order Mucorales and Aspergillus in AI IFI. As Saksenaea is the dominant fungus identified in this setting, study of the virulence characteristics and antifungal susceptibility is warranted. Disclosures: All authors: No reported disclosures.